PERAN GURU DALAM PROSES PEMBELAJARAN IPS DI KELAS VIII PADA MASA PANDEMI COVID-19 DI MTS NEGERI 1 PONTIANAK - Puspawanti Puspawanti; Sri Buwono; Achmadi Achmadi (Universitas Tanjungpura, 2022)
This study aims to determine the role of teachers in pre-learning, during learning, and post-learning in the social studies learning process in class VIII during the COVID-19 pandemic at MTs Negeri 1 Pontianak. This study used a descriptive qualitative method with data sourced from social studies teachers and class VIII students. The data collection techniques used are observation, interviews, and documentation. The results showed that the role of teachers in pre-learning was carried out in the form of gathering phone numbers and creating WhatsApp groups; ensuring the availability of smartphones and internet connection; using online learning media applications, informing lesson schedules; making lesson plans; and ensuring both parents/guardians and students support online learning. The role of the teacher during learning is carried out in the form of checking the students’ attendance, reading prayers, delivering material, and providing opportunities for students to ask questions and express opinions. Lastly, the role of the teacher in post-learning is to check the students’ tasks, remind students to collect assignments, and provide feedback in the form of appreciation for student tasks.